Temporal–spatial dynamics of typical ecosystem services in the Chaobai River basin in the Beijing-Tianjin-Hebei urban megaregion - Zhang, Jiping; Liu, Chunlan; Wang, Hui; Liu, Xiaona; Qiao, Qing (Frontiers in Ecology and Evolution, 2023)
Human demand for ecosystem services dominates ecosystem changes and impacts the temporal–spatial patterns of ecosystem services and their trade- offs. In the process of urbanization, the supply service, regulation service, and cultural service of the ecosystem are difficult to improve in synergy in the city and its surrounding areas, which is tough for urban construction and development. This study took the Chaobai River basin located in the Beijing-Tianjin-Hebei urban megaregion in northern China as the research area. The temporal and spatial changes from 2000 to 2015 of three typical ecosystem services in the study area, including food production, water conservation, and recreation, were evaluated and analyzed through modeling. The ecosystem service hotspots, service-gain areas, and service-loss areas were identified based on spatial analysis. The dynamic change mechanism of ecosystem services was explored from the perspective of land use change and hotspot analysis. The results showed that (1) recreation and food production services showed an increasing trend, while water conservation showed a fluctuating increasing trend. (2) The service-gain area was significantly larger than the service-loss area. (3) The main land use change form in the study area during the study period was the regional conversion of cultivated land to forest land and construction land, which led to the increase in water conservation services and the reduction of food production services in the corresponding patches. However, this conversion did not affect the overall improvement of the three ecosystem services in the study area. (4) Ecosystem service hotspots have gradually changed from being single-service dominant to two co-leading services. The area of food production-recreation hotspots continued to increase, indicating synergy between them. The area of water conservation-recreation hotspots continued to decrease, indicating trade-offs between them. Different types of ecosystem services improve in synergy in the Beijing-Tianjin-Hebei urban megaregion in the process of urbanization through the improvement of agricultural technology and productivity and the promotion of leisure and sightseeing agriculture. This provides an example for other cities.